A novel ROS1 G2032 K missense mutation mediates lorlatinib resistance in a patient with ROS1-rearranged lung adenocarcinoma but responds to nab-paclitaxel plus pembrolizumab. (May 2020) - Zhou, Yuling; Jiang, Wenjuan; Zeng, Liang; Mi, Jinye; Song, Lianxi; Lizaso, Analyn; Mao, Xinru; Yang, Nong; Zhang, Yongchang
Highlights: ROS1 G2032 K mutation is a solvent-front mutation which mediates resistance to lorlatinib. Our patient with acquired ROS1 G2032 K somatic mutation responded to Nab-paclitaxel plus Pembrolizumab. Rebiopsy and NGS analysis after treatment failure could guide treatment strategies. Abstract: Introduction: ROS1 -rearranged non-small cell lung cancer (NSCLC) has demonstrated promising response to lorlatinib; however, no targeted therapy is available after failure of lorlatinib and information on acquired resistance mechanisms mediating lorlatinib resistance among ROS1 -rearranged NSCLC patients is limited. We report a ROS1 -rearranged NSCLC patient who responded to immunochemotherapy after acquisition of ROS1 G2032K-mediated lorlatinib resistance. Methods: Next-generation sequencing (NGS) was performed on supraclavicular lymph nodes (SLN) and blood samples obtained from the 53-year old male patient with advanced CD74-ROS1 -rearranged NSCLC. In vitro experiments with patient-derived SLN tumor cells and in silico homology modeling were performed to investigate mechanisms of G2032K-mediated inhibitor resistance. Results: NGS analysis revealed the detection of an acquired ROS1 G2032 K after failure from lorlatinib. Homology modeling revealed the conformational change in the inhibitor binding site induced by the ROS1 G2032 K that disrupted lorlatinib binding. In vitro experiments using patient-derived cells bearing concurrent CD74-ROS1 -rearrangement and ROS1 G2032 K demonstrated half-maximal inhibitory concentration IC50 of 730.2 nM for lorlatinib, 812.1 nM for entrectinib, and 1546 nM for crizotinib, indicating resistance to these inhibitors. With PD-L1 expression of TPS 30 %, nab-paclitaxel plus pembrolizumab was administered as fifth-line treatment and achieved partial response, with sustained response ongoing for 7 months as of January 31, 2020. Conclusion: ROS1 G2032 K is a novel mutation that mediates resistance to lorlatinib. With the lack of targeted therapeutic options after lorlatinib resistance, checkpoint inhibitor plus chemotherapy may be considered as a treatment option in patients with ROS1 -rearranged NSCLC.